2021
DOI: 10.1002/rcs.2326
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the short‐term outcomes of biportal robot‐assisted lobectomy

Abstract: Background:The present study aimed to assess the short-term consequences of biportal robot-assisted lobectomy, validating its safety and effectiveness. Methods: A retrospective analysis evaluated the clinical data and short-term results of 18 patients in the single medical group of the centre who underwent biportal robot-assisted lobectomy plus lymph node dissection from November 2020 to March 2021. Results: Lobectomy and lymph node dissection could be successfully accomplished in all 18 patients with the assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Yang and colleagues already reported and experience with the D-RATS approach, with 18 cases, considering it a safe and feasible technique (15). Watanabe and colleagues in their work describe 20 cases of planned D-RATS for anatomical pulmonary resections, with no need for conversions to thoracotomy and no need for extra ports (16).…”
Section: Discussionmentioning
confidence: 99%
“…Yang and colleagues already reported and experience with the D-RATS approach, with 18 cases, considering it a safe and feasible technique (15). Watanabe and colleagues in their work describe 20 cases of planned D-RATS for anatomical pulmonary resections, with no need for conversions to thoracotomy and no need for extra ports (16).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al reported a 3-arm biportal approach with an arm port in the 8th intercostal space on the posterior axillary line and 2 arms (camera included) and assistant access in a 4 cm incision in the 6th intercostal space on the anterior axillary line, as schematically shown in Fig. 7 [ 28 ]. Another interesting case series was published by Qu et al on 3-arm biportal robotic sleeve lobectomies, with a similar approach, but accesses shifted upwards of one intercostal space [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Even more recent techniques such as biportal and uniportal RATS have performed well with satisfactory operative outcomes. In particular, biportal demonstrated similar operative times to standard robotic approaches and conversion rate (0%) [ 28 ] and perioperative complications were satisfying [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The pure URATS approach is defined as robotic thoracic surgery performed through a single intercostal incision, without rib spreading, using the robotic camera, robotic dissecting instruments and robotic staplers. We always recommend the transition from multiportal robotic-assisted thoracoscopic surgery (MRATS) to URATS through biportal-RATS ( 14 , 15 ), doing several anatomic resections first. It is important to differentiate a pure approach from the hybrid technique (URATS-UVATS) where the surgeon only does the dissection from the console and the assistant takes over the critical part of inserting the thoracoscopic staplers through the utility incision ( 16 ).…”
Section: Introductionmentioning
confidence: 99%